2017
DOI: 10.1016/j.str.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Human βB2-Crystallin Forms a Face-en-Face Dimer in Solution: An Integrated NMR and SAXS Study

Abstract: Summary βγ-crystallins are long-lived eye lens proteins that are crucial for lens transparency and refractive power. Each βγ-crystallin comprises two homologous domains, which are connected by a short linker. γ-crystallins are monomeric, while β-crystallins crystallize as dimers and multimers. In the crystal, human βB2-crystallin is a domain-swapped dimer, while the N-terminally truncated βB1-crystallin forms a face-en-face dimer. Combining and integrating data from multi-angle light scattering, NMR and small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 44 publications
(75 reference statements)
3
36
0
Order By: Relevance
“…In the crystal structure of βB2, dimerization occurs through domain-swapping ( Bax et al, 1990 ; Lapatto et al, 1991 ), but in the crystal lattice, dimers interact through the common QR interface to form a non-bonded lattice tetramer ( Bax et al, 1990 ; Lapatto et al, 1991 ; Smith et al, 2007 ) ( Fig 5 ). Surprisingly, a very recent study has suggested that, in solution, human βB2 forms a compact dimer thought to be a QR-based dimer without domain swapping ( Xi et al, 2017 ). As yet, there are no coordinates for this structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the crystal structure of βB2, dimerization occurs through domain-swapping ( Bax et al, 1990 ; Lapatto et al, 1991 ), but in the crystal lattice, dimers interact through the common QR interface to form a non-bonded lattice tetramer ( Bax et al, 1990 ; Lapatto et al, 1991 ; Smith et al, 2007 ) ( Fig 5 ). Surprisingly, a very recent study has suggested that, in solution, human βB2 forms a compact dimer thought to be a QR-based dimer without domain swapping ( Xi et al, 2017 ). As yet, there are no coordinates for this structure.…”
Section: Resultsmentioning
confidence: 99%
“…Since the domain swap in the crystal structure of βB2 complicates the calculation of monomer and dimer dipoles (because N- and C-domains of the QR interface are not parts of the same polypeptide chain) this was not considered. No coordinates are available for the recently described compact solution dimer for this protein ( Xi et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, human βB2crystallin has been observed in different states in solution, including a domain-swapped dimer in a crystal structure (PDB ID: 1YTQ; [35] Figure 2C) and a face-en-face dimer, without domain swapping. [36] Studies of these molecules have mostly focused on two aspects: the molecular basis of their extraordinary stability and solubility, and how changes due to mutation or post-translational modification alter their biophysical properties. The γ-crystallins have shown to be more stable than βcrystallins in solution, suggesting that the inherent stability of the Greek key motif is not the only contributor to the stability of these proteins; the interdomain interface also contributes to the overall stabilization.…”
Section: The βγ-Crystallins Share a Very Stable Foldmentioning
confidence: 99%